Breastfeeding patterns and factors associated with early weaning in the Western Amazon - Fernanda Andrade Martins; Alanderson Alves Ramalho; Andréia Moreira de Andrade; Simone Perufo Opitz; Rosalina Jorge Koifman; Ilce Ferreira da Silva (Revista de Saúde Pública, 2021)
ABSTRACT OBJECTIVE: To characterize breastfeeding patterns in the first six months of life and factors associated with early weaning in a birth-cohort in Rio Branco, state of Acre. METHODS: This is a prospective study with all babies born between April and June 2015. The mothers were interviewed soon after birth and between 6 and 15 months postpartum. At hospital discharge, breastfeeding was defined as exclusively (EBF), and breastfeeding (BF). In the follow-up, breastfeeding patterns were exclusive breastfeeding (EBF), predominant breastfeeding (PBF), and breastfeeding (BF). The interruption of breastfeeding in the first six months was classified as early weaning. The Kaplan Meier method (log-rank: 95%) was used to estimate the conditional probability of change in breastfeeding pattern, and early weaning risk. Crude and adjusted proportional Cox regression models, and their respective 95% confidence intervals (95%CI), were used to analyze the factors associated with early weaning. RESULTS: The study included 833 infants in EBF (95.4%) and BF (4.6%) at hospital discharge. During the first six months of life, the infant likely discharged in EBF remaining in EBF, becoming PBF, and BF, were respectively 16.4%, 32.3%, and 56.5%. The weaning likely at six months was statistically higher for infants discharged in BF (47.4%) when compared with those discharged in EBF (26%). Factors associated with early weaning were BF at hospital discharge (HR = 1.82; 95%CI 1.06–3.11), no mother cross-breastfeeding (HR = 2.50; 95%CI 1.59–3.94), pacifier use (HR = 6.23; 95%CI 4.52–8.60), less than six months of breastfeeding intention (HR = 1.93; 95%CI 1.25–2.98), lack of breastfeeding in the first hour of life (HR = 1.45; 95%CI 1.10–1.92), and pregnancy alcohol consumption (HR = 1.88; 95%CI 1.34–2.90). CONCLUSION: Compared to infants in EBF, those in BF at hospital discharge were more likely to wean. Public health efforts should prioritize EBF at hospital discharge, promote breastfeeding in the first hour of life, and prevent alcohol consumption risks during pregnancy, cross-breastfeeding and pacifier use.